PEMBINAAN KEPRIBADIAN ANAK MENURUT PENDIDIKAN ISLAM - Lubis, Rosimah (IAIN Padangsidimpuan, 2013)
To be consistent on Islam in every kinds of situation is one way to provide a good personality to a baby. A good personality is done earlier when inÂ pregnancy. After a birth, the baby is supposed to listen Adzan even though the baby doesnâ€™t know any what.